2015
DOI: 10.11113/jt.v77.6850
|View full text |Cite
|
Sign up to set email alerts
|

THE PERFORMANCE AND SIGNIFICANCE OF ISLAMIC REITs IN A MIXED-ASSET PORTFOLIO

Abstract: Islamic Real Estate Investment Trusts (I-REITs) have been established to enhance the Islamic Capital Market. Almost 10 years of establishment of I-REITs, it is interesting to study the performance of this Islamic property investment vehicle because it is a potential and unique asset class that not fully explored. This paper examines the risk-adjusted performance analysis and correlation analysis between I-REITs in a mixed asset portfolio. The time period of study is from November 2008 to December 2014. I-REITs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…They also found that Islamic REITs provide a better risk-adjusted option for a portfolio than all other asset classes. Similarly, Rozman et al (2015) find that Islamic REITs have low correlation with shares and bonds. They suggest that Islamic REITs could potentially offer diversification enhancement to the portfolios of investors in these two assets classes.…”
Section: Islamic Real Estate Investment Trusts In Malaysiamentioning
confidence: 88%
“…They also found that Islamic REITs provide a better risk-adjusted option for a portfolio than all other asset classes. Similarly, Rozman et al (2015) find that Islamic REITs have low correlation with shares and bonds. They suggest that Islamic REITs could potentially offer diversification enhancement to the portfolios of investors in these two assets classes.…”
Section: Islamic Real Estate Investment Trusts In Malaysiamentioning
confidence: 88%
“…For example, Dewandaru et al (2017) focus on the development of I-REITS which will consequently provide the diversification advantages to potential investors, since there are very limited available I-REITs in global market with mostly established in Malaysia. The preliminary studies find that I-REITs perform better (Newell & Osmadi, 2009;Rozman et al, 2015) and have lower systematic risk (Razali & Sing, 2015) compared to conventional REITs.…”
Section: Performance Of Islamic Mutual Fundsmentioning
confidence: 96%
“…While Shariah REITs have similar characteristics as conventional REITs, such as low risk, defensive characteristics and provide diversification benefit, those characteristics of Shariah REITs are enhanced during the global financial crisis. Razali and Sing 2015 Rozman et al (2015) compared the portfolios between Shariah compliant and non-compliant REITs in Malaysia also found that the compliant portfolios outperformed the non-compliant portfolio over a 10-year period from 2004 to 2014 on both an equal-weighted and value-weighted basis. They argued that this was because of the specialist nature of the assets held by Islamic REITs in Malaysia that was mainly concentrated in the plantations and healthcare sector.…”
Section: Islamic Finance and Reitsmentioning
confidence: 98%
“…Furthermore, the past decade has seen an increasing application of REITs as a vehicle for Shariah investments. This is particularly among smaller scale individual Islamic investors and smaller Islamic funds that would not otherwise be able to acquire large-scale commercial real estate (Rozman, Azmi, Mohd Ali, & Mohamed Razali, 2015).…”
Section: Introductionmentioning
confidence: 99%